Hospitalidade no turismo voluntário: produção científica em língua inglesa (2000-2015) - SANTOS, Diego Ribeiro (2016)
Volunteer tourism or “voluntourism” is considered one of the branches of alternative tourism, in which the traveler moves around not only to seek leisure, but also to practice altruism through volunteering, assisting communities which are considered vulnerable in social projects, cultural or environmental preservation. This exploratory-descriptive research project, in the form of a documental study, aimed to understand how hospitality permeates the volunteer tourism scientific production, from the analysis of journal articles published in English language on the international database Scopus from 2000 to 2015. Theoretical foundation consisted of approaching the different conceptions of hospitality, its convergence with volunteering, the tourists’ profiles and motivations, describing the phenomenon’s impact. The search terms “volunteer tourism” and “voluntourism” resulted in the initial sample of 149 articles, which was explored according to its publishing aspects, using the content analysis to have the data processed. The production reached its peak in 2014 and most of the publishing was held in England, the United States and Netherlands, with particular reference to the Journal of Sustainable Tourism. The study of article titles, abstracts and keywords allowed the identification of themes and sub-themes, being the articles initially grouped into general themes and then according to its direct, indirect and nonexistent relation with hospitality. From the final sample of 24 articles directly related to hospitality, four analysis categories were defined: experience and hospitality, intercultural exchange and hospitality, motivation and hospitality and impact and hospitality. It was found the presence of hospitality to the understanding of the relationships between the volunteer tourists and the members of the host communities, the exchanges among individuals with different cultural background, the altruism and the personal goals as motivational factors to the practice of volunteer tourism.